1994
DOI: 10.1038/369321a0
|View full text |Cite
|
Sign up to set email alerts
|

BH1 and BH2 domains of Bcl-2 are required for inhibition of apoptosis and heterodimerization with Bax

Abstract: Bcl-2 was isolated from the t(14;18) chromosomal breakpoint in follicular B-cell lymphoma. Bcl-2 has the unique oncogenic role of extending cell survival by inhibiting a variety of apoptotic deaths. An emerging family of Bcl-2-related proteins share two highly conserved regions referred to here as Bcl-2 homology 1 and 2 (BH1 and BH2) domains (Fig. 1). This includes Bax which heterodimerizes with Bcl-2 and when overexpressed counteracts Bcl-2. We report here that site-specific mutagenesis of Bcl-2 establishes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
865
4
17

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,242 publications
(915 citation statements)
references
References 28 publications
29
865
4
17
Order By: Relevance
“…The results showed that the mI-3 and the DC22 mutants are e ective in this regard. It was previously shown that the mI-3 mutation causes Bcl-2 to lose its capacity for heterodimerization with Bax (St. Clair et al, 1997;Yin et al, 1994) and Bid (Wang et al, 1996). The ability of the mI-3 Bcl-2 mutant to inhibit Bcl-x Sinduced cell death thus demonstrates that this mutation does not eliminate the anti-apoptotic e ect of Bcl-2, at least with respect to apoptosis induced by Bcl-x S .…”
Section: Effect Of Bcl-2 Mutants On Bcl-x S -Induced Cell Deathmentioning
confidence: 95%
See 2 more Smart Citations
“…The results showed that the mI-3 and the DC22 mutants are e ective in this regard. It was previously shown that the mI-3 mutation causes Bcl-2 to lose its capacity for heterodimerization with Bax (St. Clair et al, 1997;Yin et al, 1994) and Bid (Wang et al, 1996). The ability of the mI-3 Bcl-2 mutant to inhibit Bcl-x Sinduced cell death thus demonstrates that this mutation does not eliminate the anti-apoptotic e ect of Bcl-2, at least with respect to apoptosis induced by Bcl-x S .…”
Section: Effect Of Bcl-2 Mutants On Bcl-x S -Induced Cell Deathmentioning
confidence: 95%
“…Mutations within the BH1 domain of Bcl-2 [G145A(mI-3) and G145E (mI-4)] have been shown to eliminate the Bcl-2 death repressor activity in several apoptotic systems, and to disrupt Bcl-2 heterodimerization with Bax (Yin et al, 1994). The Bcl-2DC22 mutant, on the other hand, reportedly provides partial protection from cell death and is capable of interacting with Bax (Oltvai et al, 1993).…”
Section: Effect Of Bcl-2 Mutants On Bcl-x S -And Bax-induced Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant nonfunctional BCL2 still dimerizes with wild-type BCL2, suggesting that BCL2 and BCL-X L must dimerize with BAX to display their anti-apoptotic activity. 85,88 However, the amino acid residues within BH1 and BH2 that are involved in maintaining the antiapoptotic activity of BCL2 and BCL-X L are partially different. Moreover, the cell death protective function of BCL-X L has been demonstrated in the absence of heterodimerization with BAX or BAK.…”
Section: Figurementioning
confidence: 99%
“…Other pro-apoptotic members, such as Bid and Bad, possess only the BH3 domain (Adams and Cory, 1998). Mutational analyses indicated that the BH1 and BH2 domains of Bcl-2 and Bcl-X L are required for heterodimerization with Bax to antagonize Bax's pro-apoptotic activity (Yin et al, 1994). The BH3 domain of Bax was shown to be essential for dimerization (both homo-and hetero-) and for its apoptosis-inducing ability (Zha et al, 1996).…”
Section: Introductionmentioning
confidence: 99%